Tricuspid atresia 1c accompanying neonatal encephalopathy treated with pulmonary trunk banding and therapeutic hypothermia - Yuchen Cao; Jun Shibasaki; Tsuyoshi Tachibana (Wolters Kluwer Medknow Publications, 2023)
The influence of therapeutic hypothermia, known to improve neurodevelopmental outcomes in neonatal encephalopathy, remains unknown in newborns with severe congenital heart diseases. We report a neonate with tricuspid atresia type 1c suffering from moderate neonatal encephalopathy. A burst suppression pattern on amplitude-integrated electroencephalography recovered after inducing moderate therapeutic hypothermia, but exacerbated pulmonary overcirculation still persisted even after the rewarming. Since the medical treatment for pulmonary overcirculation had reached the limit, semi-urgent pulmonary trunk banding was performed on the 4th day of life. Postoperative brain magnetic resonance imaging showed no apparent brain injuries; the patient was discharged uneventfully. We share our perioperative management experience of a patient with tricuspid atresia type Ic who required therapeutic hypothermia for neonatal encephalopathy.